2013 statement on human papillomavirus DNA test utilization. Issue 2 (24th December 2013) - Davis Davey, Diane; Goulart, Robert; Nayar, Ritu; ,
Abstract : This statement from the Cytopathology Education and Technology Consortium summarizes appropriate and inappropriate uses of human papillomavirus testing in cervical cancer screening based on guidelines from the American Society for Colposcopy and Cervical Pathology and the American Cancer Society.